Profil penyimpanan dan pemeriksaan mutu obat di Puskesmas Mutiara Kisaran - Mila Febrina Rindayani; Nur’aini Dalimunthe (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background: Storage of Pharmaceutical Supplies is a regulatory activity for Pharmaceutical Supplies that are received so that they are safe (not lost), protected from physical and chemical damage, and the established requirements maintain their quality. Pharmaceutical preparations are drugs, medicinal materials, traditional medicines, and cosmetics. Objective: To determine the storage and quality inspection of medications at the Mutiara Health Center in Kisaran. Method: This type of research is descriptive observation research. Results: Mutiara Health Center has a separate drug warehouse from the service building. The space inside the drug storage is arranged according to the U flow so that it makes it easier for officers to move. The warehouse clerk's desk is placed near the warehouse exit. It is integrated with the medicine storage room because it is not partitioned, there is no particular workspace for the warehouse, and it has sufficient ventilation. Conclusion: The drug storage system at the Mutiara Health Center in Kisaran warehouse in 2019 is in the excellent category with a percentage value of 85% consisting of 80% spatial arrangement, 80% method of drug storage, 90% stock card recording, and 90% quality observation